The effect of accelerated aging on the color stability and translucency of novel zirconia reinforced rice husk dental composite resin in different infusion media - Lin, Galvin Sim Siang; Ghani, Nik Rozainah Nik Abdul; Ismail, Noor Huda; Noorani, Tahir Yusuf (Brazilian Dental Science, 2021)
Objective: To compare the color stability and translucency of aged and unaged experimental zirconia reinforced rice husk nanohybrid composite resin (Zr-Hybrid) with a commercialized nanofilled and a microhybrid composite resin after immersion in four different infusion media. Material and Methods: Three groups of standardized disc-shaped composite resin with 80 samples per group were prepared as follow: Group 1 (Filtek-Z350-XT), Group 2 (Zmack-Comp), and Group 3 (Zr-Hybrid). Each group was further subdivided into aged (n=40) and unaged (n=40) groups. Initial color measurements were taken using a digital spectrophotometer based on CIE L*a*b* color system. Samples in aged subgroup were subjected to 2500 thermal cycles. Subsequently, all samples were immersed in four different types of infusion media (n=10): T1 - Distilled water, T2 - Soft drink, T3 - Tea and T4 - Coffee. After 15 days, color measurements of all samples were measured again. Data were analyzed using two-way ANOVA followed by Bonferroni and paired sample t-tests with a significance level set at P=0.05. Results: Unaged Zr-Hybrid showed comparable color change to Zmack-Comp and Filtek-Z350-XT (P=0.181), but aged Zr-Hybrid demonstrated the lowest color change (P<0.001). Zr-Hybrid exhibited the lowest translucency value (P<0.001), but no significant color and translucency changes (P=0.051 and P=0.069, respectively) were observed between unaged and aged Zr-Hybrid. Soft drink had the greatest effect (P<0.001) on color change, while coffee showed the greatest effect (P<0.001) on translucency. Conclusion: Although Zr-Hybrid showed greater opacity, it still retained its color stability and translucency after accelerated aging compared to commercialized microhybrid and nanofilled composite resins. All infusion media caused discoloration and affected the composite resins’ translucency. KEYWORDS Rice husk; Color stability; Composite resin; Translucency; Zirconia.